Falsos cognatos francês-português entre termos de estatutos sociais - Teles, Letícia Bonora [UNESP]; Barros, Lidia Almeida [UNESP] (My University, 2010)
In this article we address the search for equivalents in the elaboration of a model dictionary for sworn translators of terms used in bylaws, in the Portuguese-French translation direction. We present, specifically, some cases in which the morphological similarity between the two languages can lead to errors, for example false cognates.

Neste trabalho abordamos a busca por equivalentes na elaboração de um modelo de dicionário de termos de estatutos sociais para tradutores juramentados, na direção tradutória português-francês. Mostramos, mais especificamente, casos nos quais a semelhança morfológica entre as duas línguas pode conduzir a erros, como os falsos cognatos.
Keywords: Terminologia bilíngue; Tradução Juramentada; Equivalência lexical; Bilingual Terminology; Sworn Translation; Lexical equivalence